Application of combined multimodal neuroimaging and video-electroencephalography in intractable epilepsy patients for improved post-surgical outcome prediction. Issue 3 (March 2022) - Kong, Y.; Cheng, N.; Dang, N.; Hu, X.-B.; Zhang, G.-Q.; Dong, Y.-W.; Wang, X.; Gao, J.-Y.
Abstract : AIM: To investigate the ability of a multidisciplinary approach that combines multimodal neuroimaging with video-electroencephalography (v-EEG) to predict post-surgical outcomes in patients with intractable epilepsy, and explore prognostic predictors for these patients. MATERIALS AND METHODS: Fifty-eight patients with intractable epilepsy who underwent surgery between March 2016 and October 2019 were reviewed retrospectively. Demographic, clinical, v-EEG, neuroimaging, surgical, and regular follow-up seizure outcome data were collected. Forty-six patients with a follow-up of at least 12 months were graded by Engel scores. Univariate and multivariate analyses were applied to explore prognostic factors that could predict post-surgical seizure outcomes. RESULTS: Of the 58 patients, 28 were males. The median age was 27 years, the median age at first seizure was 11 years, and the median duration of seizures was 10 years. The Kaplan–Meier log-rank test showed that regardless of whether the follow-up duration was considered, epilepsy type, v-EEG, PET/CT, image post-processing methods, and a multidisciplinary approach that combined multimodal imaging with v-EEG were all correlated with seizure outcomes. Multivariate analysis found that the multidisciplinary approach was an independent predictor of post-surgical outcomes in patients with intractable epilepsy (hazard ratio = 11.400, 95% confidence interval = 2.249–57.787, p= 0.003). CONCLUSIONS: The present study showed that the multidisciplinary approach could provide independent prognostic information for patients with intractable epilepsy undergoing surgery. This approach has strong potential for the easier selection of patients to undergo surgical treatment and accurate prognostication. Highlights: Multimodal imaging plays significant role in the use of multidisciplinary approach. This approach is helpful to more accurately select patients suitable for surgery. Multidisciplinary approach provides independent prognostic information for epilepsy. Considering the cost-benefit ratio, at least v-EEG, MRI and PET are recommended for use.